A Comparative Study of Moral Courage, Moral Distress and Anxiety of Nurses Working in COVID-19 and Non-COVID-19 Wards - Ebrahimabadi , Maryam; Abedi , Ahmad Reza; Gheiasi , Seyede Fatemeh; Rafiei , Fatemeh; Fournier, Andrew; Khosravani, Mahboobeh (Bioethics and Health Law Journal (BHL), 2026)
Moral distress and generalized anxiety disorder (GAD) due to the moral challenges of dealing with COVID-19 can reduce the quality of nursing care. In such situations, nurses require moral courage to demonstrate proper moral performance. This study aimed to compare the levels of anxiety, distress and moral courage of nurses working in COVID-19 and Non-COVID-19 wards. The study was approved by the Ethics Committee of Zanjan University of Medical Sciences (Ethical code No.IR.ZUMS.REC.1399.171). This comparative cross-sectional study was conducted on 107 nurses working in COVID-19 and Non-COVID-19 wards in the teaching hospitals of Zanjan University of Medical Sciences, Iran, in 2020. Nurses were selected by convenience sampling method. Data were collected using demographic, Professional Moral Courage (PMC) scale, Iranian Moral Distress Scale (IMDS) and GAD scale and analyzed using independent t-tests, Chi-square, Mann-Whitney and Fisher’s exact tests with p-value<0.05 in SPSS 16 software. Comparing the mean scores of generalized anxiety between nurses caring for COVID-19 and Non-COVID-19 patients, a statistically significant difference was found (p<0.05). However, there was no significant difference in the mean score of moral distress severity between nurses caring for COVID-19 and Non-COVID-19 patients (p>0.05). Similarly, no significant difference was found in the mean score of moral courage between the two groups caring for COVID-19 and Non-COVID-19 patients (p>0.05). The results showed that the level of generalized anxiety disorder in nurses of Non-COVID-19 wards is higher than COVID-19. This finding emphasized the distinct psychological impact of caring for patients with COVID-19. However, the level of moral courage and moral distress in the two groups of nurses did not differ significantly. These results imply that while the challenges related to generalized anxiety are more evident in the context of COVID-19 care, nurses in both patient groups face comparable levels of moral distress and exhibit similar levels of moral courage. Recognizing these nuanced aspects of nurses’ well-being and resilience is essential for crafting focused support strategies and interventions in healthcare settings.